Pengaruh Sikap Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Pada PT. PLN (Persero) UP3 Sibolga - Anggi Khairani; Yenni Sofiana Tambunan; Andrian Irsyan (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
The success of an organization in achieving its vision and mission greatly depends on individual and group performance. The better the employee performance, the better the overall organizational performance. This study aims to determine the effect of work attitude and workload, both partially and simultaneously, on employee performance at PT. PLN (Persero) UP3 Sibolga. This research uses a descriptive method with a quantitative approach. The sample was taken as 25% of the total population of 298 employees, resulting in 75 respondents. Data analysis was conducted using multiple linear regression. The results show that work attitude and workload contribute 49.4% to employee performance, while the remaining 50.6% is influenced by other variables not examined in this study. Simultaneously, work attitude and workload have a positive and significant effect on employee performance, as indicated by Fcount (37.090) being greater than Ftable (3.12). Partially, work attitude is the most dominant variable affecting employee performance with tcount (4.087) greater than ttable (1.993), while workload also has a positive and significant effect with tcount (2.865) greater than ttable (1.993). The regression equation obtained is Y = 17.235 + 0.378X₁ + 0.296X₂, indicating a positive relationship among variables.